ANALISIS ABNORMAL RETURN SAHAM LQ-45 SEBELUM DAN SAAT COVID-19 VARIAN OMICRON - Nadia Sri Wahyuni, (2022)
This research is in the form of quantitative research. This study aims to determine whether there is a difference between Abnormal Returns in the period before and during the COVID-19 Omicron Variant. LQ-45 shares listed on the Indonesia Stock Exchange from august 2021 to January 2022 are the objects used in this study. he population and sample in this study are companies listed on the LQ-45 shares as a whole, with a research period of 14 days per event period using 2 events to produce 28 data. This study uses Microsoft Excel for its analysis, then uses the analysis of the normality test with Shampiro-Wilk (a significance level of 0.05) for the normality test, and by conducting the t-test using SPSS. The results obtained in this study are (1) there is a difference in Abnormal Returns between before and during the COVID-19 Omicron Variant, (2) Before the occurrence of COVID-19 Omicron Variant in Indonesia there was Abnormal Return significant, (3) There was a significant no Abnormal Return at the time COVID-19 Omicron Variant. Keywords: Abnormal Return, LQ-45 Shares, Event Study.